Individual Roles of Network and Sheet Solids in Architectured Porous Materials - Yang, Nan; Fan, Siping; Zhuang, Juncheng; Zhang, Yubo; Qian, Zheng (Frontiers in Physics, 2022)
To understand the different roles played by sheet solids and network solids in complex porous biomaterials/native tissues, we designed a new kind of nature-inspired structure comprising these two solids by using triply periodic minimal surfaces and Voronoi diagrams using the CAD method and compared them with the previously reported Poisson-Voronoi (PV) solids that only comprise network solids. Here, we show that the sheet solids contribute greater stiffness and solid/void interface than the network solids, and our TPMS-Voronoi solids can improve/tune both the elastic moduli and specific surfaces even at fixed solid volume fraction and can be stiffer than the Poisson-Voronoi solids. This can directly guide the porous materials design for use in tissue engineering and aerospace.